A Brief Summary of Global WASH Interventions - Andres, Luis (World Bank, Washington, DC, 2018)
WASH practitioners and decision-makers lack evidence on the wider health and social effects of WASHinterventions needed to create a paradigm shift in the sector. A global overview and meta-analysis on the effects of different WASH interventions on different health and socioeconomic outcomes was undertaken. The results of this analysis show that evaluations of WASH interventions continue to focus predominantly on reducing diarrheal disease and there is a strong need for larger, more rigorously designed studies covering a broader scope of outcome effects. Similarly, there is a need for greater geographical representation and finally, well-trained implementing agencies to achieve the desired results.